1986
DOI: 10.1056/nejm198612113152404
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophiluria — A New Method of Detection and Definition of the Clinical Spectrum

Abstract: Eosinophiluria is considered a useful marker of drug-induced acute interstitial nephritis. However, recognition of eosinophiluria by Wright's staining is technically difficult, and the spectrum of disorders causing eosinophiluria is not completely defined. We have adapted Hansel's stain for the examination of urinary sediment. Whereas there was a variable uptake of Wright's stain by eosinophils in the urine, such eosinophils were readily recognized with Hansel's stain by the presence of bright red granules. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(36 citation statements)
references
References 7 publications
1
34
0
1
Order By: Relevance
“…Eosinophiluria tends to support the diagnosis of allergic, drug-induced AIN and is best documented with Hansel’s stain [15], although its absence should never be used to exclude the diagnosis of AIN [7, 12]. Recently, Ruffing et al [16]reported that eosinophiluria as an indicator of AIN has the sensitivity of 40% and the specificity of 72% with a positive predictive value of only 38%, revealing that it is not actually an accurate test for diagnosis of AIN.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophiluria tends to support the diagnosis of allergic, drug-induced AIN and is best documented with Hansel’s stain [15], although its absence should never be used to exclude the diagnosis of AIN [7, 12]. Recently, Ruffing et al [16]reported that eosinophiluria as an indicator of AIN has the sensitivity of 40% and the specificity of 72% with a positive predictive value of only 38%, revealing that it is not actually an accurate test for diagnosis of AIN.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms of NSAID nephrotoxicity have been described: hemodynamic acute renal failure, papillary necrosis, interstitial nephritis, nephrotic syn drome, vasculitis, hidrosaline metabolism disturban ces and hyperkalemia [6]. In our case, the anuria and eosinophiluria focused on an immunoallergic etiolo gy, although eosinophiluria is not a pathognomonic feature [7],…”
mentioning
confidence: 71%
“…67Ga scintigram was performed by gammacamera scanner (Hitachi Co., Tokyo) 24-72 h after injecting 2 mCi 67Ga per 50 kg body weight. Eosinocytes in the urine were examined using Hansel's staining method [7], especially at the early stage of onset. Immunological examinations consisted of determining serum CH50, circulating imune complexes and LST which was evaluated by the incorporation of }H-thymidine into the peripheral lympho cytes.…”
Section: Methodsmentioning
confidence: 99%